Ensino de leitura: estratégias como contribuição para formar leitores competentes - Nascimento, Ana Maria Silva e (2019)
This research reflects upon reading as a process of interaction between author, text and reader (KLEIMAN, 2004; SOLÉ, 2008) as well as the language used by people to represent their reality at the same moment they are transformed by it (GERALDI, 2006; PASSARELLI, 2012). Thus, the aim consists of presenting a proposal of reading to be taught to sixth grade students from Elementary II School. This would develop reading competence needed to raise autonomous among competent readers. Furthermore, this would create favorable conditions for students to cromprehend and interpret effiently a text with great social circulation. The present study comes from the need of more assertive mediations to teach reading as a process of significance. Investing especiffically on reading strategies might contribute, not only for teachers' of all areas practices, but also as a basis for intervention of tutor's formation-oriented proposals